Estudo fitoquímico de Hippeastrum diniz-cruziae Dutilh & Semir e Hippeastrum glaucescens (Mart.) Herb. (Amaryllidaceae) - Santos, Vanessa Dias dos (2019)
The interest in the study of the Amaryllidaceae family is related by yours relevant chemical and biological potential that has presented over the years. The objective of this work is the isolation and characterization of alkaloids present in two Brazilian species, Hippeastrum diniz-cruziae (leaves, bulbs and roots) and Hippeastrum glaucescens (bulbs). Initially, an acid-base extraction was performed in the methanolic extracts and liquid-liquid partition of the vegetal parts, obtaining the acid AcOEt and alkaloid enriched fractions. These extracts were analyzed by GC-MS and indicated to Hippeastrum diniz-cruziae 39 known alkaloids and 24 unidentified compounds. For Hippeastrum glaucescens 12 known alkaloids and 9 unknown compounds were identified. These extracts were subjected to various chromatographic separation techniques in order to isolate and purify these compounds. As a result, 5 Hippeastrum diniz-cruziae alkaloids were isolated: cruzinine (I), 7-deoxy-narciclasine (II), licoryne (III), pseudolycorine (IV) and ungiminorine (V), with cruzinine being an unpublished alkaloid of the type homolicorin, elucidated by GC-MS, one and two-dimensional NMR, Circular Dichroism and, mainly, X-ray Crystallography. This compound presented a unique characteristic within Amaryllidaceae alkaloids, evidenced by the stereochemistry of positions H-1 and H-10b. Fractions of Hippeastrum glaucescens resulted in 20 alkaloids: 2α-7-dimethoxyhomolicorine N-oxide (VI), 7-Methoxy-O-methylillorenine N oxide (VII), Candimine N-oxide (VIII), N-oxide albamaculine (IX), 2α methoxyhomolycorine (XX), 2α-hydroxyhomolycorine (XXI), albomaculine (XXII), 2α hydroxyalbomaculine (XIII), 2α, 7-dimethoxyhomolycorine (XIV), 7-Methoxy-O methyllicorine (XV), candimine (XVI), hyppeastrine (XVII), haemantidine (XVIII), 6 epihaemantidine (XIX), 11-hydroxyvitatine (XX), tazetine (XXI), pretazetine (XXII), 3 epimachrine (XXIII), trisfaeridine (XXIV) and ismine (XXV), compounds (XI), (XVIII), (XIX) and (XXII) being obtained in three mixtures. The compounds (VI), (VII) and (VIII) were isolated for the first time in this study, being identified by 1H NMR and high resolution masses. for the compound (VII) also high resolution masses. Previous studies of Hippeastrum glaucescens have indicated relevant alkaloid and biological potential, with potential inhibitory enzyme acetylcholinesterase. For Hippeastrum diniz-cruziae this is the first phytochemical study performed, and its previous report has reported its high moebicide power and low toxicity. In this sense, this evidence 26 gives great relevance in the continuation of the respective chemical and biological studies with the respective species.